Hulless barley polyphenol extract inhibits adipogenesis in 3T3-L1 cells and obesity related-enzymes - Deng, Xianfeng; Chen, Bi; Luo, Qin; Zao, Xingru; Liu, Haizhe; Li, Yongqiang (Frontiers in Nutrition, 2022)
Obesity is characterized by excessive lipid accumulation, hypertrophy, and hyperplasia of adipose cells. Hulless barley (Hordeum vulgare L. var. nudum Hook. f.) is the principal crop grown in the Qinghai-Tibet plateau. Polyphenols, the major bioactive compound in hulless barley, possess antioxidant, anti-inflammatory, and antibacterial properties. However, the anti-obesity effect of hulless barley polyphenol (HBP) extract has not been explored. Therefore, the current study assessed the impact of HBP extract on preventing obesity. For this purpose, we evaluated the inhibitory effect of HBP extract against obesity-related enzymes. Moreover, we investigated the effect of HBP extract on adipocyte differentiation and adipogenesis through 3T3-L1 adipocytes. The results demonstrated that HBP extract could inhibit α-amylase, α-glucosidase (α-GLU), and lipase in a dose-dependent manner. In addition, HBP extract inhibited the differentiation of 3T3-L1 preadipocytes by arresting the cell cycle at the G0/G1 phase. Furthermore, the extract suppressed the expression of adipogenic transcription factors such as peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein α (C/EBPα), and regulating fatty acid synthase (FAS), fatty acid-binding protein 4 (FABP4) and adipose triglyceride lipase (ATGL). It was also observed that HBP extract alleviated intracellular lipid accumulation by attenuating oxidative stress. These findings specify that HBP extract could inhibit obesity-related enzymes, adipocyte differentiation, and adipogenesis. Therefore, it is potentially beneficial in preventing obesity.